2009
DOI: 10.1097/paf.0b013e3181c15d8c
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Death Caused by Shots From Blank Cartridge

Abstract: The authors describe 3 cases of lethal injuries caused by 7.62 mm blank cartridge shots from military automatic rifle of domestic origin (AK 47, 7.62 mm). In 1 case, the cartridge was fired from a weapon that had been leaned on the head, with subsequent destruction of brain, and in other 2 cases, the weapon had been leaned on the chests, which led to destruction of heart parts. The injuries were caused by the action of striking wave of gunpowder explosion, the air blast type. The cases demonstrate that the gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Of these cases, six were fatal neck injuries similar to our case (cases 3, 5, 9, 10, 11 and 12 in Table 1). In addition to deaths by unmodified blank pistols that have been reported in the literature, Zdravkovic et al 15 recently reported three cases of lethal injuries caused by 7.62 mm blank cartridge shots from military automatic rifles of domestic origin.…”
Section: Discussionmentioning
confidence: 92%
“…Of these cases, six were fatal neck injuries similar to our case (cases 3, 5, 9, 10, 11 and 12 in Table 1). In addition to deaths by unmodified blank pistols that have been reported in the literature, Zdravkovic et al 15 recently reported three cases of lethal injuries caused by 7.62 mm blank cartridge shots from military automatic rifles of domestic origin.…”
Section: Discussionmentioning
confidence: 92%
“…Blank cartridge consists of steel cartridge case, freely poured nitrocellulose gunpowder filling and the initial powder charge primer [1,7]. Blank cartridge injuries commonly occur in "mock wars" during Army training [1,2,7].…”
Section: Discussionmentioning
confidence: 99%
“…Blank cartridge injuries commonly occur in "mock wars" during Army training [1,2,7]. Previous published articles [7,8] reported that corneal foreign bodies were chemically inert and do not excite an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations